Towards wearable and flexible sensors and circuits integration for stress monitoring - Chen, C-M; Anastasova, S; Zhang, K; Rosa, BG; Lo, B; Assender, HE; Yang, G-Z (Institute of Electrical and Electronics Engineers, 2019)
Excessive stress is one of the main causes of mental illness. Long-term exposure of stress could affect one's physiological wellbeing (such as hypertension) and psychological condition (such as depression). Multisensory information such as heart rate variability (HRV) and pH can provide suitable information about mental and physical stress. This paper proposes a novel approach for stress condition monitoring using disposable flexible sensors. By integrating flexible amplifiers with a commercially available flexible polyvinylidene difluoride (PVDF) mechanical deformation sensor and a pH-type chemical sensor, the proposed system can detect arterial pulses from the neck and pH levels from sweat located in the back of the body. The system uses organic thin film transistor (OTFT)-based signal amplification front-end circuits with modifications to accommodate the dynamic signal ranges obtained from the sensors. The OTFTs were manufactured on a low-cost flexible polyethylene naphthalate (PEN) substrate using a coater capable of Roll-to-Roll (R2R) deposition. The proposed system can capture physiological indicators and data be interrogated by Near Field Communication (NFC) and has been validated with healthy subjects, demonstrating its application for real-time stress monitoring.